2009
DOI: 10.1088/0953-4075/42/6/065103
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon cross-section measurements using an optical chopper:z-scan and two-photon fluorescence schemes

Abstract: An effective z-scan setup with a minimum thermal effect is shown for intensity-dependent measure of two-photon absorption (TPA) with high-repetition rate lasers. Use of an additional intensity modulation with an optical chopper provides enough blanking time for a high-repetition rate laser to yield equally accurate results in TPA measurements compared to a low repetition laser. Extension of this method of thermal effect management with an optical chopper to emission studies also results in good correspondence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 19 publications
0
45
0
1
Order By: Relevance
“…The thermal change of the refractive index induced by the preceding pulse can affect the measurement by the next pulse. Recently, it was shown that the third-order optical nonlinearities could be obtained by sufficiently minimizing the thermal effects from the high repetition lasers, by reducing the excitation laser pulses using an optical chopper [14][15][16]. When an optical chopper is used, its off-time windows provide sufficient time for thermal relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal change of the refractive index induced by the preceding pulse can affect the measurement by the next pulse. Recently, it was shown that the third-order optical nonlinearities could be obtained by sufficiently minimizing the thermal effects from the high repetition lasers, by reducing the excitation laser pulses using an optical chopper [14][15][16]. When an optical chopper is used, its off-time windows provide sufficient time for thermal relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…A focusing lens, with a focal length of 25 cm, is placed before the sample to focus the incident beam. The transmitted beam through the sample is measured using an open-aperture detector and the result is processed using known correlations (Equations 1 and 2) 54 in the literature to obtain the TPA cross-sections of the samples.…”
Section: Two-photon Absorption Measurementsmentioning
confidence: 99%
“…Laser pulse energy of 5.3 nJ/pulse has been used for this experiment with pulse width of 150 fs at 76 MHz. A mechanical chopper (MC1000 A, Thorlabs Inc.) at 50 % duty cycle was used to minimize the cumulative thermal effect from the train of pulses separated by 13.5 ns with an excitation wavelength of 780 nm to the sample [38]. Interferometric autocorrelation technique was used to measure the pulse width of laser pulses.…”
Section: Two-photon Induced Fluorescence Setupmentioning
confidence: 99%